FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUASAN DAN KESETIAAN WISATAWAN - Raharso, Sri (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2005)
The conceptual framework is proposed that investigates the effects of service quality, image, and price on perceptions of customer satisfaction and loyalty.Â To test the framework, validity and of reliability analysis, factor analysis, and multiple regresion are applied to data collected from 203 tourist in Bogar Botanical Garden. The result of the study indicate that service quality positively related to satisfaction and loyalty variables.Â While price and organizational image variables in the reality not have significant influence to satisfaction variable. Price variable only owning influence directly to loyalty. Besides, image variable in the reality nor have significant influence to loyalty. While satisfaction variable alone, owning weak influence to loyalty. Thereby, variable of service quality represent very dominant variable in influencingÂ customer satisfaction and loyalty.